Zmiany imion i nazwisk w latach 1945−1950 na ziemi nyskiej w świetle materiałów archiwalnych - Choroś, Monika (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2019)
The shifting of the borders and the incorporation into the Polish state a territory that had, until 1945, been part of Germany led to the re-Polonization and Polonization of personal names. Given names belonging to the German cultural sphere, including those of saints recognized and revered throughout Poland, were replaced by Polish ones.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne